MENINGKATKAN KEMAMPUAN MENULIS CERITA DENGAN MENGGUNAKAN VIDEO ANIMASI PADA SISWA KELAS VI UPT SDN 78 BALANG,DESA BONTOKASSI, KABUPATEN TAKALAR - Wiwi Aulia Firman; Risna; Syamsinah; Ika Zulfika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elementary school students' story writing abilities still face significant challenges, particularly in developing ideas, constructing coherent plots, and applying appropriate linguistic conventions. This study aims to determine the improvement in story writing skills using animated videos among sixth-grade students at UPT SDN No. 78 Balang, Bontokassi Village, Takalar Regency. The method employed was Classroom Action Research (CAR) using the Kemmis and McTaggart model with two cycles, involving 30 students, integrating the Discovery Learning model with a Deep Learning approach based on 3-5 minute animated videos. Data were collected through observation, evaluation tests, and documentation, then analyzed using a mixed-method approach. Research results showed significant improvement with average scores increasing from 83% in cycle I to 89% in cycle II, and mastery percentage dramatically surging from 18% to 80%, indicating a 62% increase. Qualitative transformation was identified through improved abilities in developing narrative ideas, constructing coherent story plots, using richer vocabulary variations, and applying linguistic conventions appropriately. Animated videos proved effective as visual stimuli facilitating understanding of intrinsic story elements while simultaneously increasing students' motivation and active participation. This study concludes that the use of animated videos in story writing instruction is highly effective in enhancing elementary school students' literacy competencies.